Light absorption of brown carbon and nitrated phenols in aerosols in a city of South Asia: From sources to atmosphere. (May 2023) - Yan, Juping; Wang, Xiaoping; Gao, Shaopeng; Gong, Ping; Liu, Xiaobo; Xu, Tianli; Dotel, Jagdish; Pokhrel, Balram
Abstract: Nitrated phenols (NPs) are important components of the brown carbon (BrC) aerosols emitted from biomass burning and vehicle emissions. BrC affects the climate through the absorption of sunlight. Previous studies have reported the emission factors and optical properties of BrC from both primary sources and aerosols. However, the contribution of NPs to the absorption of radiation by BrC in aerosols from primary emission sources and ambient aerosols in South Asia, one of the most polluted regions worldwide, is not well known. We systematically investigated the optical properties and components of BrC from emission sources to atmosphere, and found that the major light-absorbing NPs in BrC from biomass burning (e.g., 4-nitrocatechol and methyl-nitrocatechols) were different from those from vehicle emissions (e.g., 2, 6-dimethyl-4-nitrophenol and methyl-nitrophenols), which confirmed that the optical properties of BrC depend on the fuel type of the primary source. The contribution of ∑NPs to methanol-soluble brown carbon (MS-BrC) ( f ∑NPs/MS-BrC (365nm) ) in ambient aerosols in Nepal (1–15%) was significantly higher than the value of f ∑NPs/MS-BrC (365nm) from primary sources (0.1–2.0%). This indicates that future research should focus on the light absorption properties and climatic effects of NPs in ambient aerosols. Graphical abstract: Image 1 Highlights: Optical properties of BrC aerosols from sources and in atmosphere were determined. The absorption capacities of BrC decreased from sources to atmosphere. Contribution of NPs on the light absorption of BrC aerosols were up to 15%.